1991
DOI: 10.1042/bj2780659
|View full text |Cite
|
Sign up to set email alerts
|

The importance of alcohol dehydrogenase in regulation of ethanol metabolism in rat liver cells

Abstract: We used titration with the inhibitors tetramethylene sulphoxide and isobutyramide to assess quantitatively the importance of alcohol dehydrogenase in regulation of ethanol oxidation in rat hepatocytes. In hepatocytes isolated from starved rats the apparent Flux Control Coefficient (calculated assuming a single-substrate irreversible reaction with non-competitive inhibition) of alcohol dehydrogenase is 0.3-0.5. Adjustment of this coefficient to allow for alcohol dehydrogenase being a two-substrate reversible en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Whereas studies agree that in the rat, under steady-state conditions, 50 -60% of the maximal capacity of ADH is used to oxidize ethanol (2,19), in humans the maximal activity of ADH does not appear to constitute a major rate-limiting step in the metabolism of ethanol. This is seen in well-conducted studies showing that the rate of ethanol metabolism is only minimally changed or is unchanged in individuals who carry the ADH1B*2 allele (5, 18), encoding an ADH that in vitro has a maximum activity that is one order of magnitude greater than that encoded by ADH1B*1 (9).…”
Section: Discussionmentioning
confidence: 87%
“…Whereas studies agree that in the rat, under steady-state conditions, 50 -60% of the maximal capacity of ADH is used to oxidize ethanol (2,19), in humans the maximal activity of ADH does not appear to constitute a major rate-limiting step in the metabolism of ethanol. This is seen in well-conducted studies showing that the rate of ethanol metabolism is only minimally changed or is unchanged in individuals who carry the ADH1B*2 allele (5, 18), encoding an ADH that in vitro has a maximum activity that is one order of magnitude greater than that encoded by ADH1B*1 (9).…”
Section: Discussionmentioning
confidence: 87%
“…Seule une ponction de sang au niveau de la veine sus-hépatique aurait permis d'observer une concentration veineuse supérieure à la concentration artérielle. À forte dose d'éthanol (3 g.kg −1 ), les concentrations en acétates présentent un plateau traduisant une saturation des mécanismes enzymatiques de production (métabolisme de l'éthanol et de l'acétaldéhyde) [37,38] et/ou d'élimina-tion (métabolisme de l'acétate). Une action inhibitrice de l'éthanol sur l'alcool-déshydrogénase soit directe, soit par l'intermédiaire de son premier métabolite, l'acétaldéhyde, a été rapportée [37,[39][40][41].…”
Section: Discussionunclassified
“…Cependant la vitesse d'élimina-tion de l'éthanol ne semble pas corrélée aux concentrations d'acétaldéhyde [42] et la consommation des cofacteurs enzymatiques ne semblent pas, non plus, limiter le métabolisme de l'éthanol [37]. Plus récemment, l'hypothèse que l'alcool déshydrogénase puis l'aldéhyde déshydrogénase puissent limiter le métabolisme de l'éthanol a été avancée [38].…”
Section: Discussionunclassified
“…34 A third point of view proposes that there is not a single rate‐limiting step in ethanol metabolism, and that control is shared among several steps. 35 These controversies notwithstanding, Ronis et al recently demonstrated that a significant proportion of alcohol‐mediated liver injury occurs independently of alcohol metabolism. 36 Our results, showing that KO mice develop severe steatosis despite a significant block in hepatic ethanol metabolism, are consistent with their study.…”
Section: Discussionmentioning
confidence: 99%